1976
DOI: 10.1520/jfs10344j
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Abuscreen® for Methadone

Abstract: In recent years radioimmunoassay has provided the toxicologist with a rapid, simple way to identify and quantitate drugs of abuse. This paper deals with an evaluation of a radioimmunoassay for methadone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Manning et al (22) reported a lethal methadone concentration ranging from 0.4 mg/L to 1.8 mg/L. In 22 of our cases, death was attributed to methadone toxicity alone, with 3 cases having no other drugs present and only one having a concentration of another drug above the therapeutic range.…”
Section: Discussionmentioning
confidence: 54%
“…Manning et al (22) reported a lethal methadone concentration ranging from 0.4 mg/L to 1.8 mg/L. In 22 of our cases, death was attributed to methadone toxicity alone, with 3 cases having no other drugs present and only one having a concentration of another drug above the therapeutic range.…”
Section: Discussionmentioning
confidence: 54%
“…This threshold (T3) corresponds to lethal concentrations found in different organs (brain, kidney and liver) sampled on humans intoxicated by methadone. The threshold of lethality (minimum) ranged from 0.5 mg/g (brain) to 1.8 mg/g (liver) with a maximum average at 3.8 mg/g [23]. This cut-off (T3) could be used as threshold for human fatality but should be confirmed in future studies.…”
Section: Quantitative Analysis Of Pupae Reared On Methadone Spiked Sumentioning
confidence: 92%
“…Spiked concentrations were selected based on reports of human fatalities [23] and on the previous works by Hecht et al [16] and Strehler et al [18]. Each meat batch was mixed in a Waring blender (VWR, Leuven, Belgium) for 5 min at ambient temperature to ensure a uniform spread of methadone.…”
Section: Necrophagous Fly Experimentsmentioning
confidence: 99%
“…Determination of methadone in urine, blood and tissue by radioimmunoassay is described (Coumbis and Kaul 1974;Manning et al 1976 …”
Section: Discussionmentioning
confidence: 99%